Preparation of a novel photocatalyst for photo-degradation of bio-refractory organic contaminants in water - Leow, Shijie. (2012)
This project aims to develop a novel photocatalyst for the effective photo-degradation of bio-refractory organic contaminants in water. Conventional pure TiO2 photocatalyst exhibits certain drawbacks such as requiring UV light irradiation due to its wide band gap energies, limiting its practical application and hindering commercialization. There exists a critical need to modify TiO2 as to enhance its visible light utilization and photocatalytic efficiency.